Hemangiopericytoma of the cervical spine - Raghvendra V Ramdasi; Trimurti D Nadkarni; Naina A Goel (Journal of Craniovertebral Junction and Spine, 2014)
A 28-year-old male presented with neck pain and dysesthesias in the right upper limb. On examination, he had a firm, well-defined midline posterior cervical mass discernible on palpation at the mid-cervical level. He had no neurological deficit. Neuroradiology revealed a variegated enhancing cervical mass is arising from C3 lamina. The mass extended into the right extradural space eroding the C3 lamina and posteriorly into the intermuscular plane. The tumor was excised totally. Histopathology of the tumor showed features of hemangiopericytoma (HPC). The patient underwent postoperative radiotherapy. Primary osseous spinal HPC are rare malignant extra-axial tumors that tend to recur and metastasize. Only two cases of primary osseous HPC have been reported earlier to involve the cervical spine. The clinical presentation and management of the present case with a review of the literature is presented.